Natural products in antibiotic development: is the success story over?. (December 2022) - Bernal, Freddy A; Hammann, Peter; Kloss, Florian
Abstract : Natural product (NP)-based antibiotics have been exploited for more than eighty years and continue saving uncountable lives every year. However, antimicrobial R&D is inadequate to counteract antimicrobial resistance. The majority of marketed antibiotics are inspired by NP classes that were discovered more than 50 years ago. With the advent of advanced genomic approaches, cultivation methods, and modern analytical techniques, NP discovery holds promise that there are way more powerful antibiotic scaffolds to be discovered. However, the currently lean antibiotic R&D pipeline shows a clear trend away from NP-based programs and innovative compounds are also rare in early stages. Within this review, we give an overview of the current NP antibiotic development pipeline, elaborate constraints the field is facing, and suggest measures to streamline NP-based antibiotic discovery. It is unlikely that NPs have lost significance, but reinforcement of discovery will require more targeted efforts and support to revitalize this established source. Graphical Abstract: ga1